261 Engineering Synthetic Scaffolds to Achieve Periodontal Ligament Cell-Mediated Tissue Regeneration. (April 2022) - Fraser, David; Benoit, Danielle
Abstract : OBJECTIVES/GOALS: Autologous periodontal ligament cells (PDLCs) are a promising tool for rebuilding tooth-supporting (periodontal) tissues but require scaffolds that enable delivery while maintaining PDLC bioactivity. The goal of this study was to design a synthetic hydrogel that fulfilled these criteria to support clinical translation of PDLC delivery. METHODS/STUDY POPULATION: Hydrogels were formed using poly(ethylene glycol) (PEG) polymers and synthetic peptides. PDLCs were isolated from human 3rd molars following informed consent and were cultured using established techniques. Integrin-binding peptides were utilized to promote specific PDLC behaviors, testing PDLCs from 3 human donors in a design of experiments (DOE) approach. Two promising hydrogel designs, identified in the DOE, were selected for validation testing using PDLCs from 3 additional donors. Finally, a small animal model for hydrogel-mediated PDLC delivery was used to determine if benchtop outcomes could predict in vivo tissue regeneration. RESULTS/ANTICIPATED RESULTS: Hydrogel scaffolds maintained high PDLC viability and controlled differentiation of each donor's PDLCs based on differential presentation of integrin-binding peptides RGD and GFOGER. Two hydrogel designs were selected that optimized either PDLC alkaline phosphatase (ALP) activity or matrix mineralization, outcomes typically associated with cementum and bone formation. ALP activity-optimized hydrogels displayed enhanced PDLC pyrophosphate regulation while mineralization-optimized hydrogels promoted PDLC osteogenic differentiation. When used to deliver PDLCs to periodontal defects, both ALP activity-optimized and mineralization-optimized hydrogels stimulated new cementum formation with inserting PDL fibers, while mineralization-optimized hydrogels promoted enhanced bone formation. DISCUSSION/SIGNIFICANCE: Numerous challenges remain for translating PDLC regenerative potential to clinical practice. This study demonstrates that a synthetic hydrogel scaffold could overcome certain barriers, including controlling PDLC bioactivity with a simplified fabrication and delivery scheme, and may be a promising scaffold for periodontal tissue regeneration.